Efficacy of lower-limb muscle training modalities in severely dyspnoeic individuals with COPD and quadriceps muscle weakness: results from the DICES trial. Issue 6 (7th January 2014) - Sillen, Maurice J H; Franssen, Frits M E; Delbressine, Jeannet M L; Vaes, Anouk W; Wouters, Emiel F M; Spruit, Martijn A
Abstract : Rationale: Strength training and neuromuscular electrical stimulation (NMES) improve lower-limb muscle function in dyspnoeic individuals with chronic obstructive pulmonary disease (COPD). However, high-frequency NMES (HF-NMES) and strength training have never been compared head-to-head; and effects of low-frequency NMES (LF-NMES) have never been studied in COPD. Therefore, the optimal training modality to improve lower-limb muscle function, exercise performance and other patient-related outcomes in individuals with severe COPD remains unknown. Objectives: To study prospectively the efficacy of HF-NMES (75 Hz), LF-NMES (15 Hz) or strength training in severely dyspnoeic individuals with COPD with quadriceps muscle weakness at baseline. Methods: 120 individuals with COPD (FEV1 : 33±1% predicted, men: 52%, age: 64.8±0.8 years) were randomised to HF-NMES, LF-NMES or strength training as part of a comprehensive inpatient pulmonary rehabilitation programme. No treadmill walking or stationary cycling was provided. Measurements and main results: Groups were comparable at baseline. Quadriceps muscle strength increased after HF-NMES (+10.8 Newton-metre (Nm)) or strength training (+6.1 Nm; both p<0.01), but not after LF-NMES (+1.4 Nm; p=0.43). Quadriceps muscle endurance, exercise performance, lower-limb fat-free mass, exercise-induced symptoms of dyspnoea and fatigue improved significantly compared with baseline after HF-NMES, LF-NMES or strength training. The increase in quadriceps muscle strength and muscle endurance was greater after HF-NMES than after LF-NMES. Conclusions: HF-NMES is equally effective as strength training in severely dyspnoeic individuals with COPD and muscle weakness in strengthening the quadriceps muscles and thus may be a good alternative in this particular group of patients. HF-NMES, LF-NMES and strength training were effective in improving exercise performance in severely dyspnoeic individuals with COPD and quadriceps weakness. Trial registration: NTR2322